Secure network coding scheme for scalable video streaming - Liu, Xi-Meng; Liu, Guang-Jun; Ma, Jian-Feng; Xiong, Jin-Bo (Tongxin Xuebao, 2013)
With the purpose to achieve hierarchical security levels for scalable video streaming in heterogeneous networks, random function was used to randomize parts of the video streaming in each layer. Network coding scheme was also used to resist known-plaintext attacks. Moreover, network encoder was studied. Ordered random linear network encoder was designed for scalable video transmission. It could achieve scalability in security levels with few random operations and reduce communication overhead. Analysis shows that the scheme could effectively increase the network throughput.